Immune reconstitution inflammatory syndrome after withdrawal of Natalizumab? - Lenhard, Thorsten; Biller, Armin; Müller, Wolf C.; Metz, Imke; Schönberger, J.; Wildemann, Brigitte (Neurology, 2010)
Natalizumab, a humanized monoclonal antibody directed against the very late activating antigen-4, prevents lymphocyte transmigration across endothelium in multiple sclerosis (MS).1 It is undefined whether cessation of treatment carries the risk of disease exacerbation. A postwithdrawal rebound in T2-weighted lesional activity has been described after short-term exposure, whereas another study reported stable findings up to 14 months after discontinuation of natalizumab.2 We report a patient who developed dramatic clinical and radiologic worsening as a consequence of natalizumab withdrawal after prolonged therapy. Several features were reminiscent of an immune reconstitution inflammatory syndrome (IRIS). - - ### Case report. - - A 30-year-old woman had been diagnosed with relapsing-remitting MS in 1999 and had received glatiramer acetate and interferon-β as disease-modifying agents before natalizumab was started as escalating therapy because of continuing relapses (3-4/year; Expanded Disability Status Scale score [EDSS] 5). Natalizumab effectively reduced disease activity to 3 mild clinical events within a treatment period of almost 2 years (22 infusions). A cranial MRI 4 months after institution of therapy showed no new or active lesions (figure, A and B). In November 2008, natalizumab was discontinued because of a wish to have children. At that time, the disease was clinically stable. The patient was able to manage her everyday life with mild support and was employed half-time as an office clerk (EDSS 5). Within 9 weeks after natalizumab withdrawal, she progressively developed high-grade tetraparesis despite repeated IV steroid pulses (methylprednisolone 8.5 g in total). This coincided with multiple new T2-weighted and gadolinium-enhancing lesions in …
Gesehen am 13.03.2023